Understanding the psychosocial impact of the COVID-19 pandemic on Latinx emerging adults - Jaramillo, Natalia; Felix, Erika D. (Frontiers in Psychology, 2023)
There is growing evidence about the potential negative psychosocial impact of the COVID-19 pandemic on ethnoracially minoritized young adults. Emerging adulthood is a developmental stage (ages 18-29 years old) that is characterized by identity exploration, instability, self-focus, feeling “in between” and having a sense of possibilities. Latinx emerging adults have reported significant socio-emotional consequences as a result of the COVID-19 pandemic. The aim of this study was to explore the psychosocial impact of the COVID-19 pandemic on Latinx emerging adults (N = 31; ages 18-29) in California and Florida through online focus group interviews. A qualitative constructivist grounded theory approach was used in an effort to develop empirical knowledge, as research on the psychosocial impact of the COVID-19 pandemic on Latinx young adults is limited. This method served to capture the richness of the experiences of participants by allowing analytic codes and categories to drive theory development. In total, seven focus groups were held and participants attended a virtual focus group with other Latinx emerging adults from their state. The focus groups were transcribed verbatim and coded using constructivist grounded theory. Five themes were identified from the data concerning the impact of the pandemic on Latinx emerging adults, which centered around mental health experiences, navigating family factors, pandemic-related communication, career and academic disruptions, and systemic and environmental factors. A theoretical model was constructed to generate an understanding about factors influencing psychosocial functioning for Latinx emerging adults during the pandemic. The study has implications for advancing science on the consequences of pandemics on mental health and cultural considerations that may influence disaster recovery. Examples of these cultural considerations that emerged from this study include multigenerational values, heightened responsibilities, and mediating pandemic information. Results can inform efforts to increase support and resources for Latinx emerging adults in order to address the psychological difficulties resulting from the COVID-19 pandemic.